Williams–Beuren Syndrome as a Potential Risk Factor for Burkitt Lymphoma - Kimura, Ryo; Ishii, Yuko; Tomiwa, Kiyotaka; Awaya, Tomonari; Nakata, Masatoshi; Kato, Takeo; Okazaki, Shin; Heike, Toshio; Hagiwara, Masatoshi (Frontiers in Genetics, 2018)
Williams–Beuren syndrome (WBS) is a multisystemic neurodevelopmental disorder caused by a hemizygous deletion on chromosome 7q11.23. Though at present there is a limited number of reports on WBS patients with tumors, most cases are related to blood cancer in children with WBS. We describe a case of Burkitt lymphoma in a 21-year-old man with WBS. In addition to providing a summary of published reports describing tumors observed in patients with WBS, we present a hypothesis about a possible mechanism of oncogenesis. In particular, we identified some significantly dysregulated cancer-related genes using blood samples from this patient at the age of 19 years (who have not yet developed Burkitt lymphoma). Our findings may provide a new perspective on the relation between WBS and Burkitt lymphoma.